1999
DOI: 10.2166/wst.1999.0150
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of Constructed Wetlands to Remove Parasite Eggs from Wastewaters in Egypt

Abstract: The use of Gravel Bed Hydroponic (GBH) constructed wetlands for wastewater treatment and reuse in semi-arid climates has been evaluated in Egypt with respect to the removal of parasite eggs from domestic wastewaters. Influent and effluent from established 100m GBH reed beds receiving partially treated wastewater, were analysed to establish daily parasite loading rates and removal performance of the system under normal operating conditions (201/min; intermittent 12h on/off flow regime.) The syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Removal of helminth eggs from water, mainly wastewater, has been attempted using many different sanitary engineering processes such as stabilization ponds (Jimenez 2007), constructed wetlands (Rivera et al 1995;Stott et al 1999), coagulation-flocculation (Jimenez et al 2001;Jimenez 2003;Mara 2003), filtration (Landa et al 1997;Jimenez et al 2001;Riahi et al 2009), and UASB (Diaz et al 1991;Von Sperling et al 2002) which have demonstrated the achievement of a helminth egg removal rate of 80-100% within 20-35 h of treatment. Although the main source, wastewater is not the only matrix where helminth eggs can be present, several studies have reported dealing with the presence of these pathogens in surface eind even ground water (Diaz et al 1991;Geldreich 1998;Esrey et al 2000;Blumenthal et al 2001;Ashbolt 2004;Cifuentes et al 2004), and it is well documented that they possess high resistance to disinfection, resisting treatments and emerging live from domestic taps (Bertolucci et al 1998;Campos 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Removal of helminth eggs from water, mainly wastewater, has been attempted using many different sanitary engineering processes such as stabilization ponds (Jimenez 2007), constructed wetlands (Rivera et al 1995;Stott et al 1999), coagulation-flocculation (Jimenez et al 2001;Jimenez 2003;Mara 2003), filtration (Landa et al 1997;Jimenez et al 2001;Riahi et al 2009), and UASB (Diaz et al 1991;Von Sperling et al 2002) which have demonstrated the achievement of a helminth egg removal rate of 80-100% within 20-35 h of treatment. Although the main source, wastewater is not the only matrix where helminth eggs can be present, several studies have reported dealing with the presence of these pathogens in surface eind even ground water (Diaz et al 1991;Geldreich 1998;Esrey et al 2000;Blumenthal et al 2001;Ashbolt 2004;Cifuentes et al 2004), and it is well documented that they possess high resistance to disinfection, resisting treatments and emerging live from domestic taps (Bertolucci et al 1998;Campos 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Constructed wetlands have been specifically identified as a technology to be used in developing countries to reduce sewage pollution (e.g. Abdel-Shafy et al 2009;Liu et al 2009;Demont 2006;Belmont et al 2004;Whitney et al 2003;Stott et al 1999;Campbell and Ogden 1999;Denny 1997;Panswad and Chavalparit 1997;Juwarkar et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The plants typically used are as follows: (a) large plants with floating or aerial leaves; (b) plants with well-developed and submerged roots, such as rushes, water hyacinth, reeds, and water lilies; and (c) very small floating plants with few roots or no roots at all, such as those of the Lamenacea family, Lemna or duckweed, Spirodela, Wolffia, Wolffiela, and Salvinia [77,78]. Most of the removal of helminth eggs occurs within the first 25 m in a horizontal flow gravel bed wetland (100 m long), reaching 100% after the entire process [79,80].…”
Section: Wastewater Treatment Processesmentioning
confidence: 99%